The Ambivalent Impact of Digital Technology on Loneliness: Navigating Connection and Isolation in the Digital Age - Cahyono, Maria Yuni Megarini; Adiawaty, Susi (Yayasan Sinergi Kawula Muda, 2024)
Loneliness and social isolation have gained increasing attention as significant public health concerns, exacerbated by the COVID-19 pandemic. This study explores the psychological, social, and demographic dimensions of loneliness, emphasizing its impact on mental health and well-being. A systematic literature review was conducted using multiple academic databases, including PubMed, Scopus, and Web of Science. The findings confirm that loneliness is strongly associated with depression, anxiety, and psychological distress, with young women and older adults being particularly vulnerable. Digital technology has played a dual role, offering both social support and, in some cases, reinforcing social disconnection. Regional disparities highlight that economic insecurity and limited healthcare access further exacerbate social isolation in developing nations. The discussion emphasizes the importance of targeted policy interventions, including community-based programs, mental health integration into primary healthcare, and public awareness campaigns. Technology should be used strategically to enhance social connectivity rather than replace face-to-face interactions. The study identifies key research gaps, such as the need for longitudinal studies to assess the long-term impact of loneliness and intervention effectiveness. Future research should explore the intersection of loneliness with socioeconomic determinants to develop holistic, evidence-based strategies for mitigating its effects. Addressing loneliness requires a multifaceted, collaborative approach integrating social, economic, and technological solutions to enhance overall well-being.